2007
DOI: 10.2961/jlmn.2007.01.0010
|View full text |Cite
|
Sign up to set email alerts
|

Laser Direct Write of Active Thin-Films on Glass for Industrial Flat Panel Display Manufacture

Abstract: New high repetition rate picosecond lasers offer possibility for high efficiency structuring of transparent conductors on glass and other substrates. The results of ablation of the indium-tin oxide (ITO) layer on glass with picosecond lasers at various wavelengths are presented. Laser radiation initiated ablation that formed trenches in ITO. Profile of the trenches was analyzed with a phase contrast optical microscope, a stylus type profiler, SEM and AFM. Clean removal of the ITO layer with the 266 nm radiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…By considering the two physical mechanisms, i.e., free carrier collective oscillation and excitation from intermediate levels between conductive and valence bands, we were able to achieve successful processing at low laser energy, i.e., 2 J/cm 2 . This is even lower than the process energy of ITO thin film (2.8 J/cm 2 ) that is currently used in practical PDP manufacturing [5,6]. This result implies that laser processing on SnO 2 thin films can potentially achieve significantly higher speed and low cost in practical manufacturing.…”
Section: Properties Of the Yag Laser Processing On Sno 2 -System Thinmentioning
confidence: 96%
See 2 more Smart Citations
“…By considering the two physical mechanisms, i.e., free carrier collective oscillation and excitation from intermediate levels between conductive and valence bands, we were able to achieve successful processing at low laser energy, i.e., 2 J/cm 2 . This is even lower than the process energy of ITO thin film (2.8 J/cm 2 ) that is currently used in practical PDP manufacturing [5,6]. This result implies that laser processing on SnO 2 thin films can potentially achieve significantly higher speed and low cost in practical manufacturing.…”
Section: Properties Of the Yag Laser Processing On Sno 2 -System Thinmentioning
confidence: 96%
“…Laser processing of materials located on the top line partially or completely failed even with 12 J/cm 2 of laser energy. As reference, representative values of ITO and Cr thin film are also shown on the graph [5,6]. Figure 4 shows that materials whose carrier concentration is near λ p could be processed.…”
Section: Properties Of the Yag Laser Processing On Sno 2 -System Thinmentioning
confidence: 99%
See 1 more Smart Citation
“…The successful patterning of ITO on glass substrates by using Excimer laser 248 nm has been reported by many researchers. Some authors demonstrate the enormous commercial potential of Laser Direct Write (LDW) versus wet-etch lithography for the patterning of ITO on glass for the manufacturing of Plasma Display Panels (PDPs) 6 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] In recent years, laser direct imaging (LDI) has been developed to produce the surface texturing, scribing, marking, grooving, depositing, milling, cutting, drilling, and patterning on various materials. Henry et al 5) indicated an optimum industrial fluence of 2.8 J/cm 2 irradiated on ITO thin films with a thickness of 100 nm that could obtain high quality ITO patterns. The process time for a 42'' plasma display panel (PDP) could be less than 20 s fabricated by the laser direct writing technology.…”
Section: Introductionmentioning
confidence: 99%